Age-dependent integration of cortical progenitors transplanted at CSF-neurogenic niche interface - Greene, Gretchen; Pothayee, Nikorn; Jahanipour, Jahandar; Jie, Hyesoo; Tao-Cheng, Jung-Hwa; Petrus, Emily; Maric, Dragan; Koretsky, Alan P. (Frontiers in Cell and Developmental Biology, 2025)
There has been renewed interest in neural transplantation of cells and tissues for brain repair. Recent studies have demonstrated the ability of transplanted neural precursor cells and in vitro grown organoids to mature and locally integrate into host brain circuitry. Most studies have focused on how the transplant behaves and functions after the procedure, but the extent to which the host brain can properly innervate the transplant, particularly in the context of aging, is largely unexplored. Here we report that transplantation of rat embryonic cortical precursor cells into the cerebrospinal fluid-subventricular zone (CSF-SVZ) interface of adult rat brains generates a brain-like tissue (BLT) at an ectopic site. This model allows for the assessment of precursor cell development, cellular interactions, and graft-host connectivity as a function of host age. We found that the transplanted precursor cells initially proliferated, then differentiated, and developed into mature BLTs, which received supportive cellular components from the host including blood vessels, microglia, astrocytes, and oligodendrocytes. There was integration of the BLT into the host brain which occurred at all ages studied, suggesting that host age does not affect the maturation and integration of the precursor cell-derived BLT. Long-range axonal projections from the BLT into the host brain were robust throughout the different aged recipients. However, long-distance innervation originating from the host brain into the BLT significantly declined with age. This work demonstrates the feasibility and utility of integrating new neural tissue structures at ectopic sites into adult brain circuits to study host-transplant interactions.